ТЕХНОЛОГИЯ ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШДА УЛАРНИНГ ХАЛҚ ҲУНАРМАНДЧИЛИГИ БЎЙИЧА КОМПЕТЕНЦИЯЛАРИНИ РИВОЖЛАНТИРИШ - Тажиев, Ж.К. (SCIENCE and SOCIETY, 2020)
The article gives information about the work on solution of the problems that occur during the process of teaching the subject "Handicraft and artistic designing" in Bachelor direction of "Technology" in higher education. The author gives suggestions about development of future teachers’ competencies in technology of in handicraft and applied art.
Keywords: handicraft; applied art; artistic designing; competence; technology